Optimization of Electrically Controlled Permanent Magnet Synchronous Machine to Improve Flux Control Range - Paplicki, P. (Elektronika ir Elektrotechnika, 2014)
This paper presents the design, analysis, control, optimization and experimental evaluation of an Electrically Controlled Permanent Magnet Excited Synchronous Machine (ECPMSM) possessing field-control capability. In order to increase flux control range of the machine a three-dimensional finite element analysis (3-D FEA) and the GOT-It software optimization tool are used. The experimental results of no-load back electromotive force (back-EMF) waveform of the prototype machine and a comparison between the analysis and test results are also presented. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.5934